The economics of carp farms in Poland - K. Turkowski; A. Lirski (Acta Ichthyologica et Piscatoria, 2010)
Background. Polandis one of the largest common carp producers in the European Union. By 2006, the annual production of carp and other cyprinid fish species had reached around 17 000 t. The economic efficiency of pond farms is not only significant for the performance of Poland’s traditional carp market, but it also supports the non-productive environmental functions of earthen carp ponds. The objective of this study was to determine the costs and revenues of carp ponds, and to identify the key conditions for improving the profitability of carp farming in Poland. Materials and methods. Data from 2005–2007 were collected through a survey of 18 carp farms keeping full accounting records of a total pond area of 17-302 ha, accounting for around 34% of the total in Poland. Data was both biological and economic. The former consisted of survival rate of different age groups of fish. The latter included farm revenues (sales of carp and other species, angling fees, and other income sources) and annual production costs. The cost was separated into two main parts, variable- and fixed costs. The income was determined by subtracting the annual total cost from the total revenue. The profitability was defined as the cost-to-income ratio. The results were compared with available economic indicators of carp production in Germany and Hungary in 1999-2002. Results. The proceeds from the sale of market-size carp had a predominant share of total revenues of the investigated farms. The variable cost consisted of labour (37%) and feed (20%), while the share of the remaining cost components did not exceed 10% of total expenses of fish farms. Only in 2007 was pond fish production profitable (merely 3.95%) while in 2005 and 2006, the total costs of the farms were higher than their revenues (on average –7.42% and –2.42%, respectively). The average survival rates of stocking carp in the studied farms, including fry between 0 and 2 years of age, were very low at 36% and 38%, respectively. The survival rates of market-size carp were much higher, on average 67%. Conclusion. The economic situation of Polish carp farms, within the studied time period, was difficult. The low survival rates of stocking carp seemed to be one of the main causes for the low return on carp production. This may be a compound effect not only of epizootic diseases but also of piscivorous animals and environmental restrictions imposed on carp ponds.Farmers could find it difficult to reconcile fish production with the pond environmental functions and the need to maintain a healthy profit margin without external financial support.